Assessing the role of genome-wide DNA methylation between smoking and risk of lung cancer using repeated measurements: the HUNT study. (17th March 2021) - Sun, Yi-Qian; Richmond, Rebecca C; Suderman, Matthew; Min, Josine L; Battram, Thomas; Flatberg, Arnar; Beisvag, Vidar; Nøst, Therese Haugdahl; Guida, Florence; Jiang, Lin; Wahl, Sissel Gyrid Freim; Langhammer, Arnulf; et al.
Abstract: Background: It is unclear if smoking-related DNA methylation represents a causal pathway between smoking and risk of lung cancer. We sought to identify novel smoking-related DNA methylation sites in blood, with repeated measurements, and to appraise the putative role of DNA methylation in the pathway between smoking and lung cancer development. Methods: We derived a nested case-control study from the Trøndelag Health Study (HUNT), including 140 incident patients who developed lung cancer during 2009–13 and 140 controls. We profiled 850 K DNA methylation sites (Illumina Infinium EPIC array) in DNA extracted from blood that was collected in HUNT2 (1995–97) and HUNT3 (2006–08) for the same individuals. Epigenome-wide association studies (EWAS) were performed for a detailed smoking phenotype and for lung cancer. Two-step Mendelian randomization (MR) analyses were performed to assess the potential causal effect of smoking on DNA methylation as well as of DNA methylation (13 sites as putative mediators) on risk of lung cancer. Results: The EWAS for smoking in HUNT2 identified associations at 76 DNA methylation sites ( P  <   5 × 10 –8 ), including 16 novel sites. Smoking was associated with DNA hypomethylation in a dose-response relationship among 83% of the 76 sites, which was confirmed by analyses using repeated measurements from blood that was collected at 11 years apart for the same individuals. Two-step MR analyses showed evidence for a causal effect of smoking on DNA methylation but no evidence for a causal link between DNA methylation and the risk of lung cancer. Conclusions: DNA methylation modifications in blood did not seem to represent a causal pathway linking smoking and the lung cancer risk.